METAKOGNISI SISWA DALAM PEMECAHAN MASALAH TRIGONOMETRI - Dimas Femy Sasongko; Subanji Subanji; I Made Sulandra (FMIPA UNIVERSITAS NEGERI MALANG, 2018)
Metacognition is an influencing factor in mathematical problem solving. The aim of this qualitative research is to comprehend metacognition from one student of High Problem Solving Achiever (HPSA) and one student of Low Problem Solving Achiever (LPSA) when solving trigonometry problems that focused on metacognitive awareness, metacognitive regulation, and metacognitive evaluation aspects. The finding indicates that in metacognitive awareness, LPSA has difficulty to model the problem. In metacognitive regulation, the global plan, local plan, and actions which composed by LPSA didn’t tend to the solution. In metacognitive evaluation, eventhough LPSA did lots of metacognition activities but it didn’t guarantee achieving correct solution